2007
DOI: 10.1016/j.juro.2007.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence Estimation, Risk Factors and Characterization of Chronic Prostatitis/Chronic Pelvic Pain Syndrome in Urological Hospital Outpatients in Italy: Results of a Multicenter Case-Control Observational Study

Abstract: The prevalence and estimated incidence of chronic prostatitis/chronic pelvic pain syndrome in urological hospital outpatients in Italy are high. The syndrome is closely related to lifestyle, diet, smoking, gastrointestinal or anorectal disease and impaired sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 15 publications
6
115
0
11
Order By: Relevance
“…Urinary symptoms [9,11,[17][18][19][20] Cohort studies report ≥1 LUTS symptom in 39-68% of patients [17,18]. There may also be an association with recurrent UTIs in a minority of patients [19,21] Voiding LUTS (weak stream, straining and hesitancy) Storage LUTS (urgency AE urge incontinence, increased urinary frequency, nocturia and dysuria) Urethral burning during, and independent of, micturition Haematospermia (blood in semen) Recurrent UTI (more applicable to CBP) Sexual dysfunction symptoms [17,[22][23][24][25][26][27][28][29][30] Findings from cohort studies (n = 130-1 800) indicate that total or partial ED is reported by 15-55% of patients with CP/CPPS [22,[31][32][33][34], while the prevalence of overall, self-reported sexual dysfunction is higher at 46-92% [22,23,31,34].…”
Section: Clinical Assessment and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary symptoms [9,11,[17][18][19][20] Cohort studies report ≥1 LUTS symptom in 39-68% of patients [17,18]. There may also be an association with recurrent UTIs in a minority of patients [19,21] Voiding LUTS (weak stream, straining and hesitancy) Storage LUTS (urgency AE urge incontinence, increased urinary frequency, nocturia and dysuria) Urethral burning during, and independent of, micturition Haematospermia (blood in semen) Recurrent UTI (more applicable to CBP) Sexual dysfunction symptoms [17,[22][23][24][25][26][27][28][29][30] Findings from cohort studies (n = 130-1 800) indicate that total or partial ED is reported by 15-55% of patients with CP/CPPS [22,[31][32][33][34], while the prevalence of overall, self-reported sexual dysfunction is higher at 46-92% [22,23,31,34].…”
Section: Clinical Assessment and Diagnosismentioning
confidence: 99%
“…There may also be an association with recurrent UTIs in a minority of patients [19,21] Voiding LUTS (weak stream, straining and hesitancy) Storage LUTS (urgency AE urge incontinence, increased urinary frequency, nocturia and dysuria) Urethral burning during, and independent of, micturition Haematospermia (blood in semen) Recurrent UTI (more applicable to CBP) Sexual dysfunction symptoms [17,[22][23][24][25][26][27][28][29][30] Findings from cohort studies (n = 130-1 800) indicate that total or partial ED is reported by 15-55% of patients with CP/CPPS [22,[31][32][33][34], while the prevalence of overall, self-reported sexual dysfunction is higher at 46-92% [22,23,31,34]. Correlation studies of sexual dysfunction symptoms with NIH-CPSI scores indicate that patients with CP/CPPS with sexual dysfunction have higher total and QoL scores, suggesting that sexual symptoms can contribute substantially to morbidity [28,[31][32][33]35,36].…”
Section: Clinical Assessment and Diagnosismentioning
confidence: 99%
“…Acute and chronic prostatitis, prostatodynia, or chronic pelvic pain syndrome (CPPS) is associated with ED, PE and painful ejaculation (114)(115)(116)(117)(118). This syndrome includes urogenital pain, ejaculatory pain, urinary dysfunction, and sexual dysfunction.…”
Section: Pe and Chronic Prostatitismentioning
confidence: 99%
“…Mú sculo elevador del ano parte superior o puborrectal Etiología y mecanismos de producció n de la lesió n Se encuentran patrones de tensió n muscular cró nica desde la infancia (abuso sexual 18 , estreñ imiento cró nico 19 , entrenamiento para la danza, estré s, etc. ).…”
Section: Pg Internos Del Suelo Pélvico Su Típico Dolor Referido Y Suunclassified
“…El estilo de vida, la dieta, fumar, las disfunciones sexuales y las alteraciones anoré ctales entre otras situaciones está n ínti-mamente relacionadas con este síndrome. Por tanto, estamos ante un fenó meno mucho má s importante de lo esperado 19 . Un estudio de Krieger del 2004 sobre la clasificació n, epidemiología e implicaciones de la prostatitis cró nica en EEUU, Europa y Asia merece un vistazo pues aclara una serie de puntos oscuros como su frecuencia real, 2-10% de los hombres adultos y que un 15% sufre síntomas de prostatitis en algú n momento de su vida 20 .…”
Section: Epidemiologíaunclassified